Vascular and hepatic enhancements at MR imaging: comparison of Gd-EOB-DTPA and Gd-DTPA in the same subjects - Lin, Yen-Heng; Hwang, Ruey-Ming; Chen, Bang-Bin; Hsu, Chao-Yu; Yu, Chih-Wei; Kao, Jia-Horng; Lee, Hsuan-Shu; Liang, Po-Chin; Wei, Shwu-Yuan; Shih, Tiffany Ting-Fang (Clinical imaging, 2014)
The objective was to compare vascular and hepatic enhancement differences at magnetic resonance imaging (MRI) between Gd-EOB-DTPA and Gd-DTPA in the same subjects. Ten healthy subjects received dynamic contrast-enhanced MRI (DCE-MRI) with Gd-EOB-DTPA and then Gd-DTPA to obtain quantitative parameters at 60 and 100 s, respectively. At 60 s, no difference was noted in DCE-MRI parameters between the two contrast agents. At 100 s, mean transit time (MTT) was higher in Gd-EOB-DTPA than in Gd-DTPA (P=.008). Gd-EOB-DTPA showed vascular and hepatic enhancement similar to Gd-DTPA within the initial 60 s during the dynamic phase, but showed increased MTT due to hepatocytes uptake at 100 s.